A comparative between a theoretical investment portfolio and the investments practiced by a group of investors - Aguiar, Camila Camargo (2019)
The objective of this study is to compare the investments made by a group of investors with a theoretical investment portfolio in terms of performance. Through a descriptive research and quantitative approach, the study was carried out through a survey, whose research instrument was an electronic questionnaire. The sample is composed of 119 entrepreneurs from a Municipality of the State of Santa Catarina and to analyze the data was used the technique of descriptive analysis. Savings stands out as the most representative investment, with 82% of the investments practiced which indicates a predominance of the conservative profile, thus creating the theoretical investment portfolio, composed of 4 investments, where they are compared with the Interbank Deposit Certificate (CDI). The monitoring of the portfolio for the purpose of comparison with savings takes into account a period of 24 months. The return on the investment portfolio is defined by a weighted average of the investment income. In comparison, it is possible to observe the evolution of the yields in the period of 24 months, and the theoretical portfolio developed is above the CDI surpassing the 32% of profitability, however the savings in turn has 15.06% of profitability, thus making feasible the theoretical investment portfolio.